PENDIDIKAN DALAM BERBAGAI PENDEKATAN DAN TEORI PENDIDIKAN - Bintank, Bintank; Maunah, Binti (Center of Language and Cultural Studies, 2022)
Education is an important indicator to advance the nation. Education is needed to make humans into quality human beings. This is in accordance with the objectives of the State in Law No. 20 of 2003 concerning the National Education System Article 3. The role of the professional role of social workers in schools must be considered. The purpose of this research is to examine how education uses various educational approaches and theories. This research method uses the library method which is carried out by collecting data or scientific writings that aim at the object of research or data collection that is library in nature, or a study carried out to solve a problem which is basically focused on a critical and in-depth study of library materials. Relevant The problem of this research is knowing education in various educational approaches and theories. Education in Indonesia must be able to participate positively in this era of globalization, we don’t want to just be the object and month of other nations. Therefore, we must prepare ourselves as early as possible to meet this era, one alternative is to prepare human resources through the educational process.